Surgery for Type B Ankle Fracture Treatment: a Combined Randomised and Observational Study (CROSSBAT). Issue 3 (27th March 2017) - Mittal, Rajat; Harris, Ian A; Adie, Sam; Naylor, Justine M
Abstract : Background: Isolated type B ankle fractures with no injury to the medial side are the most common type of ankle fracture. Objective: This study aimed to determine if surgery is superior to non-surgical management for the treatment of these fractures. Methods: A pragmatic, multicentre, single-blinded, combined randomised controlled trial and observational study. Setting Participants between 18 and 65 years with a type B ankle fracture and minimal talar shift were recruited from 22 hospitals in Australia and New Zealand. Participants willing to be randomised were randomly allocated to undergo surgical fixation followed by mobilisation in a walking boot for 6 weeks. Those treated non-surgically were managed in a walking boot for 6 weeks. Participants not willing to be randomised formed the observational cohort. Randomisation stratified by site and using permuted variable blocks was administered centrally. Outcome assessors were blinded for the primary outcomes. Primary outcomes Patient-reported ankle function using the American Academy of Orthopaedic Surgeons Foot and Ankle Outcomes Questionnaire (FAOQ) and the physical component score (PCS) of the SF-12v2 General Health Survey at 12 months postinjury. Primary analysis was intention to treat; the randomised and observational cohorts were analysed separately. Results: From August 2010 to October 2013, 160 people were randomised (80 surgical and 80 non-surgical); 139 (71 surgical and 68 non-surgical) were analysed as intention to treat. 276 formed the observational cohort (19 surgical and 257 non-surgical); 220 (18 surgical and 202 non-surgical) were analysed. The randomised cohort demonstrated that surgery was not superior to non-surgery for the FAOQ (49.8 vs 53.0; mean difference 3.2 (95% CI 0.4 to 5.9), p=0.028), or the PCS (53.7 vs 53.2; mean difference 0.6 (−2.9 to 1.8), p=0.63). 23 (32%) and 10 (14%) participants had an adverse event in the surgical and non-surgical groups, respectively. Similar results were found in the observational cohort. Conclusions: Surgery is not superior to non-surgical management for 44-B1 ankle fractures in the short term, and is associated with increased adverse events. Trial registration number: NCT01134094.